Predictors of Post-Thrombotic Ulcer after Acute DVT: The RIETE Registry - Galanaud, Jean-Philippe; Bertoletti, Laurent; Amitrano, Maria; Fernández-Capitán, Carmen; Pedrajas, José María; Rosa, Vladimir; Barrón, Manuel; Lorenzo, Alicia; Madridano, Olga; Quéré, Isabelle; Kahn, Susan R; Prandoni, Paolo; et al. (My University, 2018)
In patients with deep-vein thrombosis (DVT) in the lower limbs, venous ulcer is the most debilitating and end-stage clinical expression of the post-thrombotic syndrome (PTS). To date, risk factors for PTS-related ulcer in DVT patients have not been identified.We used the international observational RIETE registry to assess the evolution of PTS signs and symptoms during a 3-year follow-up period and to identify independent predictors of PTS ulcer at 1 year in patients with acute DVT.Among 1,866 eligible patients, cumulative rates of PTS ulcer at 1, 2 and 3 years were 2.7% (n = 50), 4.3% (n = 54) and 7.1% (n = 60), respectively. The proportion of patients with PTS symptoms at 1, 2 or 3 years remained stable (≈40%), while the proportion of patients with PTS signs increased slightly over time (from 49 to 53%). Prior history of venous thromboembolism (VTE) (odds ratio [OR] = 5.5 [2.8-10.9]), diabetes (OR = 2.3 [1.1-4.7]), pre-existing leg varicosities (OR = 3.2 [1.7-6.1]) and male sex (OR = 2.5 [1.3-5.1]) independently increased the risk of PTS ulcer at 1 year. Obesity also increased the risk but failed to reach statistical significance (OR = 1.8 [0.9-3.3]). DVT treatment characteristics (duration or drug) did not influence the risk.Our results evidence that after acute DVT, pre-existing leg varicosities, prior venous thromboembolism, diabetes and male gender independently increased the risk for PTS ulcer. This suggests that clinicians should consider strategies aimed to prevent ulcers in high-risk DVT patients, such as preventing VTE recurrence, use of stockings in those with pre-existing venous insufficiency, careful monitoring of diabetic patients and encouraging weight loss in obese patients.